A prospective study of sexual dysfunction in patients with benign prostatic hyperplasia - P., Leelakrishna; J., Saravanan (International Surgery Journal, 2018)
Background: Benign prostatic hyperplasia (BPH)/ lower urinary tract symptoms (LUTS) patients have been found to be more prevalence of sexual dysfunction than in men with no BPH/LUTS. In this study, the authors aimed to evaluate the prevalence of sexual dysfunction in the BPH patient to see the correlation between BPH and sexual dysfunction. Methods: All patients who attended Urology outpatient department or admitted in Government Kilpauk Medical College and Hospital and Government Royapettah hospital during October 2013 to October 2014 for symptoms of BPH were enrolled for the study. Results: The prevalence of sexual dysfunction in patients with LUTS is70%. The severity of sexual dysfunction correlates with severity of LUTS. Ejaculatory function deteriorates after treatment of LUTS/BPH. Conclusions: Though the sample size is small and the follow up is limited, it can be suggested that treatment of sexual function should be combined with management of sexual dysfunction for better patient satisfaction.